A Comparative Analysis of Patients Undergoing Fusion for Adult Cervical Deformity by Approach Type. Issue 5 (June 2021) - Varshneya, Kunal; Medress, Zachary A.; Stienen, Martin N.; Nathan, Jay; Ho, Allen; Pendharkar, Arjun V.; Loo, Sheri; Aikin, Jessica; Li, Gordon; Desai, Atman; Ratliff, John K.; Veeravagu, Anand
Study Design: Retrospective cohort study. Objective: To provide insight into postoperative complications, short-term quality outcomes, and costs of the surgical approaches of adult cervical deformity (ACD). Methods: A national database was queried from 2007 to 2016 to identify patients who underwent cervical fusion for ACD. Patients were stratified by approach type—anterior, posterior, or circumferential. Patients undergoing anterior and posterior approach surgeries were additionally compared using propensity score matching. Results: A total of 6575 patients underwent multilevel cervical fusion for ACD correction. Circumferential fusion had the highest postoperative complication rate (46.9% vs posterior: 36.7% vs anterior: 18.5%, P < .0001). Anterior fusion patients more commonly required reoperation compared with posterior fusion patients ( P < .0001), and 90-day readmission rate was highest for patients undergoing circumferential fusion ( P < .0001). After propensity score matching, the complication rate remained higher in the posterior, as compared to the anterior fusion group ( P < .0001). Readmission rate also remained higher in the posterior fusion group; however, anterior fusion patients were more likely to require reoperation. At index hospitalization, posterior fusion led to 1.5× higher costs, and total payments at 90 days were 1.6× higher than their anterior fusion counterparts. Conclusion: Patients who undergo posterior fusion for ACD have higher complication rates, readmission rates, and higher cost burden than patients who undergo anterior fusion; however, posterior correction of ACD is associated with a lower rate of reoperation.